Empathy development and volunteering for undergraduate healthcare students: A scoping review. (September 2022) - Barker, Mary-Ellen; Crowfoot, Gary; King, Jennie
Abstract: Objectives: Empathy in healthcare benefits patients and healthcare providers. However, empathy decline is a recent trend within healthcare education. There is a paucity of literature that investigates the impact of volunteering on the empathy levels of undergraduate healthcare students. This scoping review explores the literature regarding empathy and volunteering for healthcare students. Design: The Joanna Briggs Institute methodology for scoping reviews guided this study. Data sources: The electronic databases MEDLINE, CINAHL, ProQuest, JBI, Cochrane, PubMed, PsychInfo, and PsychNurses were searched from January 2001 to August 2021. The original search was developed in MEDLINE and then adapted to the other databases. Review methods: This scoping review used the Joanna Briggs Institute scoping review methodology. The search retrieved a total of 310 articles. Following deduplication, 271 articles were reviewed by title and abstract. Thirty articles were reviewed in full text with twelve articles meeting the criteria for inclusion. Included studies were assessed using the Mixed Methods Appraisal Tool (MMAT). Results: Five qualitative, four quantitative and three mixed method studies were included. A variety of volunteering interventions for undergraduate healthcare students were identified from countries including the United States of America, Singapore, Australia, and Brazil. Thematic analysis identified that volunteer undergraduate healthcare students practiced and developed empathy, and experienced professional and personal development. Conclusions: Volunteering interventions were primarily in a service-learning modality within community health and palliative healthcare settings. Inconsistencies exist in empathy definitions and empirical empathy measurement. There is a need for more research that explores empathy development through volunteer activities in acute care settings.